Hubungan Karakteristik Demografi dan Pengetahuan dengan Minat Kunjungan Pasien Umum ke Pelayanan Kesehatan Tradisional di Puskesmas Sawit - Hasna Labibatunnisa Mustofa; Dwi Linna Suswardany (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Traditional health services in Indonesia continue to experience increased utilization, but there are still challenges in terms of accessibility and public understanding. Previous research has shown that there is a relationship between demographic characteristics and knowledge and patient interest in visiting, but there have not been many similar studies conducted in Boyolali Regency. Therefore, this study aims to analyze the relationship between gender, age, education level, and knowledge with general patient interest in visiting traditional health services at the Sawit Health Center, Boyolali. This study is an observational quantitative research with a cross-sectional design. A total of 95 patients were selected as samples using the convenience sampling method. The data were analyzed using the Pearson correlation test for numerical data and the Chi-square test for categorical data. The results showed that there was no significant relationship between gender and interest in visiting (p=0.402). Age (p<0.0001) and education level (p<0.0001) had a significant relationship with visiting interest, whereas older age and higher education tended to have more visiting interest. Knowledge also had a very strong correlation with patient interest in visiting (r=0.916, p<0.0001), indicating that the higher the level of knowledge of patients about traditional health services, the greater their interest in visiting the service. In conclusion, age, education level, and knowledge had a positive effect on the interest of general patients, while gender did not have a significant influence on patients' interest in visiting traditional health services at the Sawit Health Center